The influence of heating temperature and sizes of components upon stresses and defect formation in semiconductor structures under isothermal heating - Agueev, O.A.; Svetlichny, A.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
In the work a complex analysis of the influence of size of components and heating temperature upon stresses and defect formation in substrates of the Si-SiO₂ structures is done. It is determined that alteration of shape and size of components can change stresses in the silicon substrate by an order, and the increase in heating temperature from 800 to 1100 °C increases the defect formation criterion by two orders. The optimum size and shape alteration range as well as the heating temperature for defect-free thermal treatment of structures are determined.